Formas retóricas de dizer: o jornalista Celso Ming e seus artigos de opinião - Santana, Maiara Pereira de (2015)
This dissertation, produced in the line Oral and written text and discourse of the syllabus of Portuguese Language of the Pontifical Catholic University of Sao Paulo (PUC-SP), aims to do a rhetorical reading of an economic opinion article by Celso Ming appeared in the newspaper O Estado de São Paulo. For analysis purposes it is used the perspective of the rhetoric, Greek art and technique that studies the discourses used to persuade, and the opinion article, with a structure that includes an observed problem, a discussion and a solution or evaluation of the issue. Besides, it allows a rhetoric reading taking into account intra and extra text elements, such as the text composition, linguistic marks, the redactor journalist, the reader to whom the text is aimed, the author intentions. The opinion (doxa in rhetoric) promotes an interaction between the parts but a vision or ideological conception prevails. To compose the analytic base of this investigation, we have as foundation the studies of the theorists of the rhetoric areas studying the persuasive speeches and the studies of Aristotle (2005), Perelman-Tyteca (2005), Olivier Reboul (2004), Michael Meyer (2007) and Ferreira (2010). The study starts with the next questions about the act of communication through the newspaper: Whom does it attend? What is made public? What are the consequences of that rhetoric act (the text)? It is also guided by a wide and general objective (analyze through the perspective of the rhetoric the op-ed articles written by the journalist Celso Ming) and by more specific ones: identify in the articles the arguments based on the structure of the real and the authority, link the configuration of the real and the plausible. Guided by such objectives the analytical categories are: I) Identification of the rhetoric genre and question, II) Identification of the rhetoric context, III) Identification of the elements that show the problem and the solution to the problem, IV) Identification with the structure of the rhetoric discourse: inventio, dispositio, elocutio and peroration. The results are: the articles were written in a lapse of time of ten days, from the first to the 11th of January in 2011. The justification to choose texts from this period was the context of the 2008 post-crisis America and the expectative that this referent imposes in the new government being formed in Brazil. This way the rhetorical acts (the texts spread through credited ideology maker newspapers such as O Estado de Sao Paulo) made the opinion articles become influential to the readers. The analysis proves that the prevalent genre in all the articles analyzed was the rhetoric deliberation and that the audience aimed by the speaker varied between the universal and the particular in accordance with each article